Strategie pomocy dzieciom ulicy w Jaipurze. Studium przypadku organizacji I-India - Beata Pietkiewicz-Pareek (Problemy Wczesnej Edukacji, 2016)
This study examined the efforts to provide vocational training programmes for abused, orphaned, and destitute children in the capital of Rajasthan. The presented results are the effect of the larger project on illiteracy conducted by the author in India in 20121. Harmful traditional practices like child labour, child marriage, the caste system, discrimination against girl children impact negatively on children and increase their vulnerability to abuse and neglect. I-India is a fully registered, nonprofit, non-governmental organisation. It was established in 1993 and employs a staff of eighty dedicated local people. I-India’s main activities are the provision of: an information/advice help-line for children in need, repatriation of children to their families, temporary and permanent homes, medical care and sanitation, nutrition, emotional support from trained staff, education, vocational training, awareness, and advocacy.